THE ANXIETY OF FEMALE STUDENTS IN LEARNING ENGLISH - Makmun, Nadiah (ENCOUNTER, 2012)
The female students sometimes have a lot of weakness/shortage such as: they are not brave to make an opinion, the weakness of their physic, frighten and they feel that they are so weakness. But sometimes they have a lot of goodness/strength such as: patience, diligence and carefulness. Actually, the female students have a good potential in learning foreign language especially English. They are not only good at IQ but also EQ & SQ that really support to be successful in learning English. But other wise sometimes some female students are easy to feel worried and nervous. They feel week and inferior. Being worried, nervous are negative thing that sometimes appear when the learning process happens or when they use English in every opportunity. They are lack of self confidence to use/practice English. Based on the problems, the lectures/ teachers should teach not only using a good method or a good technique but also a good approach so the teaching-learning process will be successful. The teacher/lecturer should make the English class as interesting as possible by using media. It can at last reduce their anxiety and improve their self confidence. For the students, they should be able to see and control themselves from anxiety that is sometimes exist.